Teaching History in a Post-pandemic World: The Perceptions of Teachers on Training - Muñoz, Carlos; Torres, Bastián; Martínez, Rosendo; Carrillo, Olga (Frontiers in Education, 2022)
The aim of the study was to analyse the perception that teachers in training have on why and for what purpose they teach or will teach history in the era of globalization. The study is part of the project Proyecto FONDECYT Regular Nº1221872 titled El Desarrollo de habilidades de pensamiento histórico para vivir en sociedad. Tensiones, desafíos y propuestas para el sistema escolar chileno and part of the project El desarrollo de habilidades, pensamiento histórico de estudiantes de Pedagogía en Historia y Geografía de la Universidad de Concepción: un estudio de caso para la mejora de la formación inicial docente (UCO-1798). The information was collected through in-depth interviews with 30 teachers in training of both sexes from the last five cohorts. The results show that teachers in training recognise the importance of teaching history in order for people to know their culture and their past, and to commit themselves in the construction of democratic societies. Moreover, and despite the fact that they perceive their university training to be deficient, which is associated to globalization and the pandemic, teachers in training are able to identify elements and characteristics of both phenomena. This enables them to conduct historical analyses that highlight the existence of skills associated with the development of historical thinking.